A Comprehensive Solution to the Problem of the Development ofDrawing Skills with the Help of Didactic Equipment; CEUR Workshop Proceedings; Vol. 2485 : GraphiCon 2019. Computer Graphics and Vision - Vehter E. V. Eugeniya Viktorovna; Radchenko V. Yu. Valeriya Yurjevna; Shklyar A. V. Aleksey Viktorovich; Kazakova T. D. Tamara Dmitrievna (Computer Graphics, Light Engineering and Design, 2019)
Title screen